2017
DOI: 10.1038/s41598-017-05351-8
|View full text |Cite
|
Sign up to set email alerts
|

Mutual influence between current-induced giant magnetoresistance and radiation-induced magnetoresistance oscillations in the GaAs/AlGaAs 2DES

Abstract: Radiation-induced magnetoresistance oscillations are examined in the GaAs/AlGaAs 2D system in the regime where an observed concurrent giant magnetoresistance is systematically varied with a supplementary dc-current, I dc. The I dc tuned giant magnetoresistance is subsequently separated from the photo-excited oscillatory resistance using a multi-conduction model in order to examine the interplay between the two effects. The results show that the invoked multiconduction model describes the observed giant magneto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Magnetotransport studies of the ultra high mobility GaAs/AlGaAs 2DES exhibit a small and narrow negative magnetoresistance effect that appears around zero field 72 , 73 , 76 , 87 . This work aimed to follow the effect of temperature on the observed small and narrow negative magnetoresistance effect, determine whether a weak localization type line-shape analysis succeeds in describing the data, extract physical parameters, and possibly identify the physical origin of the observed effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetotransport studies of the ultra high mobility GaAs/AlGaAs 2DES exhibit a small and narrow negative magnetoresistance effect that appears around zero field 72 , 73 , 76 , 87 . This work aimed to follow the effect of temperature on the observed small and narrow negative magnetoresistance effect, determine whether a weak localization type line-shape analysis succeeds in describing the data, extract physical parameters, and possibly identify the physical origin of the observed effect.…”
Section: Discussionmentioning
confidence: 99%
“…Our magnetotransport studies have been characterized by two distinct negative magnetoresistance effects in the high quality GaAs/AlGaAs 2DES in the low magnetic field limit: (a) a negative Giant Magneto-Resistance (GMR) effect over larger magnetic fields (−0.15 ≤ B ≤ 0.15 T ) and (b) a small and narrow negative magnetoresistance effect in the immediate vicinity of null magnetic field. The dependence of the negative-GMR on the sample size, DC-bias, temperature, and also the interplay between GMR and the radiation induced magnetoresistance oscillations have been reported 72 , 76 , 87 . Here, we present the experimental study of the small and narrow negative magnetoresistance effect about B = 0.…”
Section: Introductionmentioning
confidence: 94%
“…The requirement of a dc -bias for the observability of the effect, together with the improved observability of the effect at higher bath temperatures, T ≈ 4 K, suggests that the dc -bias serves to heat the electron system, and the current heating helps to bring about the obervability of the effect. Certainly, the observed effects are fascinating and further measurements are being carried out to understand their origin, and the role of the dc -bias in the electronic system 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…As far as the dark magnetoresistance properties of high mobility GaAs/AlGaAs 2DES are concerned, our previous reports exhibit two distinct dark MR effects, which are: 1) negative Giant Magnetoresistance (negative‐GMR) effect and 2) narrow negative MR effect around B = 0 T. Experimental studies have shown that the negative‐MR effect around zero magnetic fields is temperature dependent (i.e., T ≥ 1 K) . However, another study reported a temperature (i.e., T ≤ 800 mK) invariance of the narrow negative magnetoresistance effect .…”
Section: Introductionmentioning
confidence: 91%